Predicting Affective Information – An Evaluation of Repetition Suppression Effects - Trapp, Sabrina; Kotz, Sonja A. (Frontiers in Psychology, 2016)
Both theoretical proposals and empirical studies suggest that the brain interprets sensory input based on prior expectations to mitigate computational burden. However, as social beings, much of sensory input is affectively loaded – e.g., the smile of a partner, the critical voice of a boss, or the welcoming gesture of a friend. Given that affective information is highly complex and often ambiguous, building up prior expectations of upcoming affective sensory input may greatly contribute to its rapid and efficient processing. This review points to the role of affective information in the context of the ‘predictive brain’. It particularly focuses on repetition suppression (RS) effects that have recently been linked to prediction processes. We interpret the findings as evidence for more pronounced prediction processes with affective material. Importantly, we argue that possible influences from bottom-up attention might inflate the neural RS effect, and thereby particularly overshadow the magnitude of RS for affective information. Finally, anxiety disorders, such as social phobia, are briefly discussed as manifestations of modulations in affective prediction.